Views on the Etymology of Anthroponyms Belonging to Iranian Languages in the Historical Works Created in the Persian-Tajik Language in the X-Xiii Centuries (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides information about the existence of ancient etymological views in Persian-Tajik sources, analyzes of some anthroponyms by Persian and Tajik historians who lived in the X-XIII centuries, and compares these views with today's linguistic achievements.